Eastern and Southern Africa - Collinson, Michael (International Food Policy Research Institute, 1987)
The drier monsoon tropical climate of most of eastern and southern Africa has the world's highest solar energy intake (150 to 180 Kcal per square centimeter per year). However, its potential for crop growth (48 to 57 tons per hectare dry matter per year, assuming 3 percent conversion of light energy), is never realized due to water limitations (Cooper 1970). In addition, radiation, temperature, and soils modify rainfall potentials of local areas.